A 500 U/2 mL dilution of abobotulinumtoxinA vs. placebo: randomized study in cervical dystonia. (3rd July 2018) - Lew, Mark F.; Brashear, Allison; Dashtipour, Khashayar; Isaacson, Stuart; Hauser, Robert A.; Maisonobe, Pascal; Snyder, Daniel; Ondo, William
ABSTRACT: Purpose/aim: AbobotulinumtoxinA (Dysport®, Ipsen Biopharmaceuticals, Inc., Basking Ridge, NJ, USA) is an acetylcholine release inhibitor and a neuromuscular blocking agent. The United States prescribing information for abobotulinumtoxinA previously indicated only one dilution for cervical dystonia: 500 U/1 mL. Clinical trial data supporting a larger volume with a 500 U/2 mL dilution would offer clinicians flexibility with injection volume to better meet patient needs. Materials and methods: We conducted a 12-week, phase 3b, multicenter, randomized, double-blind, placebo-controlled trial (NCT01753310). Adult subjects with a primary diagnosis of cervical dystonia were randomized (2:1) to receive a single injection of either abobotulinumtoxinA, 500 U/2 mL dilution, or placebo. The primary efficacy endpoint was changed from baseline in Toronto Western Spasmodic Torticollis Rating Scale total score at Week 4. Results: A total of 134 subjects (abobotulinumtoxinA, n = 89; placebo, n = 45) were randomized (intent-to-treat population) and 129 (abobotulinumtoxinA, n = 84; placebo, n = 45) completed the Week 4 primary endpoint evaluation (modified intent-to-treat population). In the modified intent-to-treat population, subjects receiving abobotulinumtoxinA experienced significantly greater changes from baseline versus placebo on the primary endpoint (weighted overall treatment difference −8.3, P < 0.001). The most common treatment-emergent adverse events (TEAEs) were dysphagia, muscle weakness, neck pain and headache. Overall, TEAEs were consistent with those reported in the abobotulinumtoxinA prescribing information (1 mL dilution) for cervical dystonia patients. Conclusions: This trial provides evidence that a 500 U/2 mL dilution is an effective treatment for cervical dystonia and exhibits a safety profile consistent with the known safety profile of abobotulinumtoxinA.